2010
DOI: 10.1038/ejcn.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-glucans from Agaricus bisporus on ex vivo cytokine production by LPS and PHA-stimulated PBMCs; a placebo-controlled study in slightly hypercholesterolemic subjects

Abstract: Introduction: Mushrooms are known for their immune modulating effect for which the polysaccharide fraction, mainly glucans, seem to be responsible. Fungal b-glucans have been studied extensively, whereas little is known about mushroom a-glucans. We have earlier shown that the polysaccharide fraction from the mushroom A. bisporus, consisting 90% of a-glucans, induced in vitro tumor necrosis factor (TNF)a and nitric oxide production. The purpose of this study was to evaluate the effects of consuming. Method: A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 29 publications
(30 reference statements)
2
16
0
2
Order By: Relevance
“…The streptozotocin induced diabetic male Sprague-Dawley rats fed the A. bisporus powder (200 mg/kg of body weight) for three weeks had significantly reduced triglyceride (TG) and plasma glucose concentrations to 39.1% and 24.7% respectively, liver enzyme activities, aspartate aminotransferase and alanine aminotransferase to 15.7% and 11.7% respectively, and liver weight gain (Jeong et al, 2010). Volman et al (2010) investigated the effects of alpha-glucans from A. bisporus. They reported that consumption of alpha-glucans of A. bisporus mushroom lowered producing lipopolysaccharide-induced TNFa by 69% compared to the control group, whereas no effect on IL-1b and IL-6 was observed.…”
Section: Antidiabeticmentioning
confidence: 99%
“…The streptozotocin induced diabetic male Sprague-Dawley rats fed the A. bisporus powder (200 mg/kg of body weight) for three weeks had significantly reduced triglyceride (TG) and plasma glucose concentrations to 39.1% and 24.7% respectively, liver enzyme activities, aspartate aminotransferase and alanine aminotransferase to 15.7% and 11.7% respectively, and liver weight gain (Jeong et al, 2010). Volman et al (2010) investigated the effects of alpha-glucans from A. bisporus. They reported that consumption of alpha-glucans of A. bisporus mushroom lowered producing lipopolysaccharide-induced TNFa by 69% compared to the control group, whereas no effect on IL-1b and IL-6 was observed.…”
Section: Antidiabeticmentioning
confidence: 99%
“…The authors suggested that in vivo, alpha-glucans had lost their efficacy to stimulate the immune response as observed in an in vitro mouse model (Volman, Mensink, van Griensven, & Plat, 2010a).…”
Section: 2mentioning
confidence: 98%
“…α-Glukany wykazują, potwierdzone doświadczalnie, działanie prozdrowotne. Na szczególną uwagę zasłu-guje aktywność przeciwnowotworowa, immunostymulująca oraz antyoksydacyjna [17,18]. Augustin i wsp.…”
Section: Wprowadzenieunclassified